A novel p.E121G heterozygous missense mutation of SOD1 in an apparently sporadic ALS case with a 14-year course. Issue 1 (March 2015) - Canosa, Antonio; Calvo, Andrea; Moglia, Cristina; Barberis, Marco; Brunetti, Maura; Cammarosano, Stefania; Manera, Umberto; Ilardi, Antonio; Restagno, Gabriella; Chiò, Adriano
Abstract: The frequency of SOD1 mutations differs among populations: in Italy they account for 13.6% of familial ALS and 0.7% of sporadic cases. We describe an apparently sporadic Italian ALS patient, carrying a novel p.E121G heterozygous missense mutation of SOD1, with a 14-year disease course and a prevalent lower motor neuron phenotype, which are not uncommon among SOD1 mutations carriers. To our knowledge, no other mutation of codon 121 of SOD1 has ever been reported. Three in silico models suggest a deleterious effect of the p.E121G mutation. Nevertheless, further studies are necessary to confirm its pathogenic role and to evaluate eventual genotype-phenotype correlations.